2012
DOI: 10.1155/2012/265712
|View full text |Cite
|
Sign up to set email alerts
|

Is Almond Consumption More Effective Than Reduced Dietary Saturated Fat at Decreasing Plasma Total Cholesterol and LDL-c Levels? A Theoretical Approach

Abstract: Hypercholesterolemia can be a consequence of excessive dietary saturated fatty acid (SFA), while almond-supplemented diets can improve lipid profiles. However, the differential and independent impacts of dietary SFA and almondsupplemented diets on plasma total cholesterol (pTC) and low-density lipoprotein (pLDL-c) concentrations have not been directly compared and are not well described. We reviewed the available data to construct multiple regression analyses to theoretically assess the impact of relative almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A theoretical modelling study compared the effects of relative almond intake (defined as almonds consumed per body weight) and that of reduction of dietary saturated fats alone. The study observed that increased almond intake was more beneficial 210 than by the reduction of dietary saturated alone and that replacing saturated fats with almonds on a regular basis could help reduce LDL-C levels further [41].…”
Section: Almonds and Ldl-c Levelsmentioning
confidence: 97%
“…A theoretical modelling study compared the effects of relative almond intake (defined as almonds consumed per body weight) and that of reduction of dietary saturated fats alone. The study observed that increased almond intake was more beneficial 210 than by the reduction of dietary saturated alone and that replacing saturated fats with almonds on a regular basis could help reduce LDL-C levels further [41].…”
Section: Almonds and Ldl-c Levelsmentioning
confidence: 97%
“…), soluble fibre‐containing foods, such as oats and psyllium (Ortiz et al . ; Nishi et al . ), and plant stanols and sterols (Abumweis et al .…”
Section: The Effect Of Combination Dietary Interventions On Cardiovasmentioning
confidence: 99%
“…Portfolio Diets are low-fat diets based on plant foods, specifically those plant foods or ingredients proven to reduce blood cholesterol, for example soya (Anderson et al 1995;Harland & Haffner 2008), nuts (Kris-Etherton et al 2008;Sabate et al 2010), soluble fibrecontaining foods, such as oats and psyllium (Ortiz et al 2012;Nishi et al 2014), and plant stanols and sterols (Abumweis et al 2008;Demonty et al 2009). Latterly, the diets also have included a source of monounsaturated fatty acids (MUFA) in the form of rapeseed or sunflower oil (Labonte et al 2013).…”
Section: The Effect Of Combination Dietary Interventions On Cardiovasmentioning
confidence: 99%
“…A theoretical modelling study compared the effects of relative almond intake (defined as almonds consumed per body weight) and that of reduction of dietary saturated fats alone. The study observed that increased almond intake was more beneficial than the reduction of dietary saturated alone and that replacing saturated fats with almonds on a regular basis could help reduce LDL-C levels further [ 42 ].…”
Section: Almonds and Ldl-c Levelsmentioning
confidence: 99%